Fatal Consequences of Lighter Gas Abuse: A Case Report - Çakıroğlu Ö. F.; Taşlıdere B.; Arac B. (My University, 2024)
Volatile solvent abuse among young people poses a significant public health threat due to its accessibility and fatal outcome potential. This case report presents a 22 year old otherwise healthy male who died after lighter gas abuse, which highlights the severity of inhalant abuse related outcomes. To conclude, volatile substance abuse proves to be a significant and rising problem across the globe especially among younger populations, driven by its immediate psychoactive effects and ease of access. Lighter gas is a commonly abused inhalant which contains volatile hydrocarbons that cause central nervous system and respiratory depression, cardiac arrhythmias, myocardial infarction and pulmonary edema. The exact mechanism of death associated with butane abuse is still uncertain, however research done by Pfeiffer et al. focused on acute and chronic myocardial changes, and lung histology that was similar to that of drowned persons which is characterized by capillary endothelial vesicular transformation and the development of obstructive microangiopathy. Intense nonspecific fibrosis with the absence of coronary disease with immunohistochemical analysis confirming acute ischemia was also noticed. Fatal arrhythmia is thought to arise from the inhaled hydrocarbons or 0.5-15% butane which are suspected to increase the myocardium’s sensitivity to adrenaline, and this sudden hormonal surge is thought to be the culprit for the occurrence of fatal arrhythmia, and ventricular fibrillation like in this case.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Cerrahi; Clinical Medicine (Med); Clinical Medicine; Surgery; Acil Tıp Hizmetleri; Emergency Medical Services